Advanced Bayesian Methods for Longitudinal Data Analysis in Public Health - Taha, Reem Talal; Ahmed, Saba Sabah; Y. Hatim, Qais; Abu-AlShaeer, Mahmood Jawad (Journal of Ecohumanism, 2024)
Background: Longitudinal data analysis is a crucial component of public health research because it provides information about temporal changes and the progression of health outcomes. Traditional statistical methods frequently fail to tackle the intricacies of longitudinal data, such as handling missing data, accommodating different data distributions, and incorporating prior information. Objective: This study investigates Bayesian methods for longitudinal data analysis in public health, emphasizing their advantages over traditional approaches and their applicability in real-world public health scenarios. Methods: We conducted a thorough literature research and case study analysis to compare Bayesian methods to traditional methodologies. Bayesian hierarchical models, Markov Chain Monte Carlo (MCMC) simulations, and dynamic Bayesian networks were explicitly evaluated for their ability to deal with the problems inherent in longitudinal public health data. Statistical analyses included assessments of model fit using the Deviance Information Criterion (DIC) and predicted accuracy with cross-validation. Results: The results show that Bayesian approaches are more flexible and robust in managing complicated data structures, incorporating previous information, and generating more accurate parameter estimations. For example, Bayesian hierarchical models lowered mean absolute error (MAE) by 15% compared to traditional techniques. Bayesian techniques were beneficial in dealing with missing data and modelling non-linear interactions, resulting in increased predictive performance and a 20% increase in health outcome prediction accuracy. Conclusion: Advanced Bayesian methods are a huge step forward in longitudinal data analysis in public health. Their ability to incorporate prior knowledge and adapt to complex data patterns makes them an invaluable resource for public health researchers. Future research should concentrate on creating user-friendly software and training programs to encourage the widespread application of these methodologies in public health practice.